Respostas

2014-04-05T00:05:43-03:00
N(A U B U C)=n(A) + n(B) + n(C) - n(A ∩ B) - n(A ∩ C) - n(B ∩ C) + n(A ∩ B ∩ C)
Dados:
n(A ∩ B) = 8, n(C) = 10, n(A - C) = 7, n(A ∩ B ∩ C) = 5, n(B ∩ C) = 6, n(B) = 12,
n(A ∩ C) = 7; n(A)=? (não informado) 
Determinar n(A):
(A-C) = existe em A mas não existe em C ou somente em A
(A ∩ C)= existe em A e em C ⇒existe em A
n(A)=n(A - C) + n
(A ∩ C) e n(A ∩ C)=7 e n(A - C)=7 
n(A)=7+7 ⇒n(A)=14
Determinar n(A U B U C):
n(A U B U C)=n(A) + n(B) + n(C) - n(A ∩ B) - n(A ∩ C) - n(B ∩ C) + n(A ∩ B ∩ C)
n(A U B U C)=14+12+10-8-7-6+5 ⇒n(A U B U C)=36-21+5
n(A U B U C)=20